Polyamines and the Delay in Deoxyribonucleic Acid Synthesis in Some Bacteriophage T4 Infections - Dion, Arnold S. (1971)
Escherichia coli B infected by the DD mutant of T4, am N116, is stimulated to initiate deoxyribonucleic acid accumulation by 1 to 10 mm spermidine but not by 10 mm putrescine. The syntheses of putrescine and spermidine in cells infected by T4D and the mutant are similar, although slight differences are observed in the intracellular concentration of free spermidine. Unlike r-K12 (λ) systems, am N116-infected cells do not leak polyamine.